2006
DOI: 10.1016/s0929-6646(09)60162-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Hospital-based Case Management Approach on Treatment Outcome of Patients with Tuberculosis

Abstract: Treatment of TB patients by a HBCM approach provides improved treatment outcomes compared to those without case management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Nyamathi et al conducted a randomized controlled trial of NCM in the United States (U.S.) among homeless HIV-infected persons with latent TB showing that nurse case managers increased the rate of completion of isoniazid preventative therapy (OR: 3.26; 95% confidence interval, 2.13–4.99) [33] . The same impact of NCM was identified by Lin and colleagues who demonstrated a significantly higher rate of successful TB treatment compared to patients without NCM in a hospital setting (240/277, 86.6% vs. 67/92, 72.8%; p = 0.002) [32] . Data from these studies support the use of a multifaceted, patient-centered NCM intervention to improve treatment outcomes.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Nyamathi et al conducted a randomized controlled trial of NCM in the United States (U.S.) among homeless HIV-infected persons with latent TB showing that nurse case managers increased the rate of completion of isoniazid preventative therapy (OR: 3.26; 95% confidence interval, 2.13–4.99) [33] . The same impact of NCM was identified by Lin and colleagues who demonstrated a significantly higher rate of successful TB treatment compared to patients without NCM in a hospital setting (240/277, 86.6% vs. 67/92, 72.8%; p = 0.002) [32] . Data from these studies support the use of a multifaceted, patient-centered NCM intervention to improve treatment outcomes.…”
Section: Discussionsupporting
confidence: 66%
“…Following implementation, we identified improvements in adherence to MDR-TB and HIV treatment guidelines in both the delivery and decision support domains of the CCM. Prior research has demonstrated how a NCM approach leads to significant improvements in disease management and outcomes such as improved treatment adherence, decreased psychosocial distress and reduced morbidity and mortality in diseases such as heart failure [26] , [27] , diabetes [28] , HIV [16] , [29] [31] , and drug susceptible TB [32] , [33] . Nyamathi et al conducted a randomized controlled trial of NCM in the United States (U.S.) among homeless HIV-infected persons with latent TB showing that nurse case managers increased the rate of completion of isoniazid preventative therapy (OR: 3.26; 95% confidence interval, 2.13–4.99) [33] .…”
Section: Discussionmentioning
confidence: 99%
“…The NHI has broadened payment for several disease-management programs and provided financial incentives for regular diabetes follow-up visits [19-23]. In 2001, a diabetes pay-for-performance program, known as the diabetes shared care network, was implemented [24-26].…”
Section: Introductionmentioning
confidence: 99%
“…As effective management for chronic diseases has been established, the National Health Insurance (NHI) system of Taiwan has acknowledged the value of disease screening and disease management. The NHI has broadened payment for several disease-management programs and provided financial incentives for regular diabetes follow-up visits [ 19 - 23 ]. In 2001, a diabetes pay-for-performance program, known as the diabetes shared care network, was implemented [ 24 - 26 ].…”
Section: Introductionmentioning
confidence: 99%